ENHANCEMENT OF ACTIVE COMPOUNDS PRODUCTION AND STUDYING THE GENETIC VARIATION IN CALLUS OF OREGANO BY ADDING NANOMATERIALS - A.S. Abed; A.A. Tawfiq; D. M. Majeed; E.N. Ismail (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to investigate the stimulation of the formation of phenolic compounds in callus cultures of Origanum vulgare using nanomaterials. Different combinations of plant growth regulators (NAA, BAP, and TDZ) were applied to form the calli from leaf explants. The optimal effect was achieved with a combination of 1 mg/L NAA and 0.5 mg/L BAP, which resulted in an initiation rate of 100% along with significant increase in both fresh and dry weight. The addition of silver nanoparticles (Ag-NPs) and titanium dioxide nanoparticles (TiO2-NPs) at different concentrations (1, 2, and 3 mg/L) to the culture medium led to a substantial decrease in the fresh and dry weight of calluses with a significant increase in the content of tested phenolic compounds compared to the control. The effective treatment was 2 mg/L Ag-NPs, which enhanced the production of most phenolic compounds. Additionally, the RAPD-PCR study indicated the presence of genetic variation in the callus cultures under nanoparticle stress.